Dendritic cells transfected with DNA constructs encoding CCR9, IL-10, and type II collagen demonstrate induction of immunological tolerance in an arthritis model - Fisher, Marina S.; Kurilin, Vasily V.; Bulygin, Aleksey S.; Shevchenko, Julia A.; Philippova, Julia G.; Taranov, Oleg S.; Ivleva, Elena K.; Maksyutov, Amir Z.; Sennikov, Sergey V. (Frontiers in Immunology, 2024)
Introduction: Restoring immune tolerance is a promising area of therapy for autoimmune diseases.One method that helps restore immunological tolerance is the approach using tolerogenic dendritic cells (tolDCs). In our study, we analyzed the effectiveness of using dendritic cells transfected with DNA constructs encoding IL-10, type II collagen, and CCR9 to induce immune tolerance in an experimental model of arthritis. Methods: Dendritic cell cultures were obtained from bone marrow cells of Balb/c mice. Dendritic cells (DCs) cultures were transfected with pmaxCCR9, pmaxIL-10, and pmaxCollagen type II by electroporation. The phenotype and functions of DCs were studied using enzyme-linked immunosorbent assay (ELISA) and flow cytometry. Migration of electroporated DCs was assessed in vitro. Induction of antigen-collagen induced arthritis (ACIA) was carried out according to the protocol in Balb/c mice. DCs were then administered to ACIA mice. The development of arthritis was monitored by measuring paw swelling with a caliper at different time points. The immunological changes were assessed by analyzing the content of antibodies to type II collagen using enzyme immunoassay. Additionally, a histological examination of the joint tissue was conducted, followed by data analysis. The results are as follows: DCs were obtained, characterized by reduced expression of CD80, CD86, and H-2Db (MHC class I), increased expression of CCR9, as well as producing IL-10 and having migratory activity to thymus cells. Transfected DCs induced T-regulatory cells (T-reg) and Отформатировано: Шрифт: курсив increased the intracellular content of IL-10 and TGF-β in CD4 + T cells in their co-culture, and also suppressed their proliferative activity in response to antigen. The administration of tolDCs transfected with DNA constructs encoding type II collagen, IL-10, and CCR9 to mice with ACIA demonstrated a reduction in paw swelling, a reduction in the level of antibodies to type II collagen, and a regression of histological changes. Conclusion: The study presents an approach by which DCs transfected with DNA constructs encoding epitopes of type II collagen, IL-10 and CCR9 promote the development of antigenspecific tolerance, control inflammation and reduce the severity of experimental arthritis through the studied mechanisms: induction of T-reg, IL-10, TGF-β.